Analysis on the effect of cooking activities and ventilation system on IAQ and perceived symptoms among workers at SMEs food industry / Siti Nurshahida Nazli - Nazli, Siti Nurshahida (2020)
Cooking activities are known to generate pollutants in the indoor environment which can cause adverse health effects to the occupants. Poor ventilation systems from inefficient mechanical means as well as limited openings would further affect the indoor air quality in an indoor environment to the level which is hazardous to health. Adverse health effects among occupants from poor indoor air quality include respiratory problems, fatigue, heavy-headed, headache, skin, eye and throat irritation, asthma or even death. This study aims to characterise the indoor air environment at small and medium industries which conducting cooking activities as lack of studies were identified in this sector. Three different cooking methods (frying, boiling and baking) were studied at 14 small and medium (SMEs) food industries selected in Pulau Pinang. The concentration level of IAQ parameters which include particulate matter in diameter 2.5, carbon dioxide, carbon monoxide, total volatile organic compounds as well as temperature and relative humidity were measured in-situ through working hours for two consecutive days using EVM-7 and IQ-610 Graywolf. The measurements were then compared to the available standards. Air change rate were measured and the IAQ determinants factors at the food SMEs were observed and identified. These include the cooking methods, types of ventilation systems adopted, type of fuel and cooking devices used and operations of exhaust fan. Besides that, questionnaire survey was administered among SMEs workers to identify the perceived IAQ symptoms. From the results, CO2, temperature and relative humidity were found to be higher than the standard limits permitted at the three different cooking methods. To add to that, there were inadequate air change per hour which were less than 20 ACH as required by the Factory and Machinery Act (1967) which shows major problem in SMEs food industries. IAQ perceived symptoms among workers were higher in frying food SMEs although the study found that boiling SMEs had higher number of concentration of pollutants. This study provides evidence that there is correlation between the level of IAQ parameters with types of ventilation and other determinants. From the analysis of one-way ANOVA, the concentration of IAQ parameters at the SMEs food industries were related to types of cooking methods, types of ventilation system, type of fuel and cooking devices. Operation of exhaust fan however indicate no effect on CO2 and temperature level. Through Boosted Regression Tree (BRT) analysis, CO2 indicated the highest pollutant to cause complaints by workers followed by CO, temperature and relative humidity. The IAQ in SMEs food industries were poor due to inadequate ventilation systems which affecting the health of the workers. The study indicates the need of immediate corrective actions on indoor air quality and ventilation system towards SMEs food industry. This study provides a preliminary research towards providing a proper procedure and guideline for SMEs food industries. This study also suggests that future research to focus on boiling and frying SMEs with CO2, CO, temperature and relative humidity to be given emphasize. Simulation study related to these parameters might also be considered.